Prevalence and risk of migraine headaches in adult fragile X premutation carriers. (21st February 2013) - Au, J; Akins, RS; Berkowitz‐Sutherland, L; Tang, H‐T; Chen, Y; Boyd, A; Tassone, F; Nguyen, DV; Hagerman, R
Abstract : FMR1 premutation carriers are common in the general population (1/130–260 females and 1/250–810 males) and can be affected by fragile X‐associated tremor ataxia syndrome, fragile X‐associated primary ovarian insufficiency, anxiety, depression, hypertension, sleep apnea, fibromyalgia, and hypothyroidism. Here we report the results of a pilot study to assess the prevalence and risk of migraine in FMR1 premutation carriers. Three hundred fifteen carriers (203 females; 112 males) and 154 controls (83 females; 71 males) were seen sequentially as part of a family study. A standardized medical history, physical examination and confirmation of diagnosis of migraine headaches were performed by a physician. The prevalence of migraine was 54.2% in female carriers (mean age/SD: 49.60/13.73) and 26.79% in male carriers (mean age/SD: 59.94/14.27). This prevalence was higher compared to female (25.3%; mean age/SD: 47.60/15.21; p =  0.0001) and male controls (15.5%; mean age/SD; 53.88/13.31; p =  0.0406) who underwent the same protocol and were confirmed to be negative for the FMR1 mutation by DNA testing. We hypothesize that the increased prevalence of migraine headaches in FMR1 premutation carriers is likely related to the mitochondrial abnormalities that have recently been reported. Screening for migraine should be considered when evaluating FMR1 premutation carriers in the future.